The Bandoengmooi Community’s Contribution to the Preservation of Longser Art 2010-2023: Kontribusi Komunitas Bandoengmooi dalam Melestarikan Seni Longser Tahun 2010-2023 - Alfawwaz, Muhammad Fariz; Agus Permana; Usman Supendi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Longser art, a form of traditional Sundanese performance, faces significant threats from modernization and popular culture. Since 2010, the Bandoengmooi Community has taken a proactive role in preserving this cultural heritage through performances, training programs, and cross-sector collaborations. This study explores Bandoengmooi’s contributions to longser preservation using historical methods, including heuristics, criticism or verification, interpretation, and historiography. The findings reveal that Bandoengmooi not only sustains the physical performance of longser but also revitalizes its form and meaning to remain relevant in contemporary social contexts. Their training initiatives effectively engage the younger generation, equipping them with a comprehensive understanding of longser. Simultaneously, their performances function as a platform for social critique and environmental awareness. The institutional transformation into a formal foundation in 2021 further legitimized their cultural initiatives. Bandoengmooi demonstrates that cultural preservation need not be conservative but can embrace innovative and adaptive approaches to meet modern challenges. This study underscores the crucial role of community-based initiatives in saveguarding local culture heritage, especially amid awakening state support and increasing cultural globalization